2020
DOI: 10.1016/j.heliyon.2020.e05425
|View full text |Cite
|
Sign up to set email alerts
|

Depression and the risk of adverse outcomes at 5 years in patients with coronary heart disease

Abstract: Background Cardiovascular diseases are a public health concern worldwide, with high rates of morbidity and mortality. Depression is a frequent comorbidity in coronary heart disease (CHD). It can be caused by the experience of suffering from heart disease, but it can also influence the prognosis of the CHD. The prevalence of depression in patients with cardiovascular disease is twice as high as that in the general population. Aim Assess the influence of depression in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
1
2
0
1
Order By: Relevance
“…Previous studies corroborate these findings, especially with regard to cardiovascular disease, which may also have a bidirectional association with depression [ 6 , 25 , 29 ]. Evidence from observational studies suggests that depression independently predicts incident coronary artery disease events, congestive heart failure and adverse outcomes among individuals with established cardiovascular disease [ 30 32 ].…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies corroborate these findings, especially with regard to cardiovascular disease, which may also have a bidirectional association with depression [ 6 , 25 , 29 ]. Evidence from observational studies suggests that depression independently predicts incident coronary artery disease events, congestive heart failure and adverse outcomes among individuals with established cardiovascular disease [ 30 32 ].…”
Section: Discussionsupporting
confidence: 75%
“…Specifically, patients with depression have a 1.5-fold higher risk of developing CVD than patients without depression [12]. The prevalence of CVD in patients with major depressive disorder has been estimated to be 9.9% (95% CI: 7.4-13.3), with the cardiovascular-related mortality rate being higher than that in non-depressed patients [13]. Conversely, several studies have shown a higher prevalence of major depression in patients with CVD [14]: Major depression or an increase in depressive symptoms affects 20-45% of patients with coronary artery disease [15] and 30-40% of patients with stroke [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have clearly suggested that patients with cardiovascular disease (CVD) experience increased risk for depression compared to the general population (15–20 vs. 5%), which makes them more vulnerable to physical limitations, low quality of life, recurrence, high mortality and high healthcare costs ( 18 , 19 ). There are multiple pathophysiological mechanisms that explain the association between depression and CVD that does not occur by chance, such as increased levels of inflammatory markers, impaired heart rate variability, and hypothalamic-pituitary-adrenal (HPA) axis dysfunction ( 10 , 20 ).…”
Section: Introductionmentioning
confidence: 99%